ypertensive anterior uveitis after bee sting: a case report: - Cunha, Carlos Eduardo Ximenes da; Ribeiro , Marina Viegas Moura Rezende; Soares, Ana Ramalho Gameleira; Castro , Laís Rytholz; Jucá, João Vitor de Omena (Revista de Medicina, 2023)
Uveitis is the inflammation of the uveal tract, which can cause reduced visual acuity (VA) and blindness. Its diagnosis and treatment must be done earlier in order to avoid secondary inflammatory glaucoma, a feared complication. Hymenoptera bites are a rare and rarely reported cause of uveitis, that due to the type 1 hypersensitivity reaction triggered by the peptide toxins released by these insects. The article shows the case of a 67-year-old man who presented with reduced VA and pain in his right eye after bee stings. Although adequate treatment with corticosteroids and antibiotics was instituted, the patient evolved with worsening of the condition and hypertensive anterior uveitis due to non-adhesion to the therapy, anti-inflammatory and anti-glaucoma drugs were, therefore, used to prevent permanent vision loss, showing good answer.